Exacerbation of antigen-induced arthritis in urokinase-deficient mice. - Busso, N (1998)
In rheumatoid arthritis, synovial expression of urokinase (uPA) activity is greatly increased (Busso, N., V. Péclat, A. So, and A. -P. Sappino. 1997. Ann. Rheum. Dis. 56:550- 557). We report the same effect in murine antigen-induced arthritis. uPA-mediated plasminogen activation in arthritic joints may have deleterious effects via degradation of cartilage and bone matrix proteins as well as beneficial effects via fibrin degradation. We evaluated these contrasting effects in vivo by analyzing the phenotype of uPA-deficient (uPA-/-) and control mice during antigen-induced arthritis. Joint inflammation was comparable in both groups up to day 3 and subsequently declined in control mice, remaining significantly elevated in uPA-/- mice on days 10 and 30 after arthritis onset. Likewise, synovial thickness was markedly increased in uPA-deficient mice persisting for up to 2 mo, whereas it subsided in control animals. Bone erosion was exacerbated in uPA-/- mice on day 30. By contrast, no difference in articular cartilage proteoglycan content was found between both groups. Significantly increased accumulation of fibrin was observed by day 30 in arthritic joints of uPA-/- mice. We hypothesized that synovial fibrin deposition plays a role in joint inflammation. Accordingly, defibrinogenation of uPA-/- mice by ancrod significantly decreased the sustained joint inflammation. All the above observations were reproducible in plasminogen-deficient (Pln-/-) mice. In conclusion, synovial fibrin deposition plays a role as a nonimmunological mechanism which sustains chronic arthritis.